Analisis Rasio Kebangkrutan Perusahaan pada Masa Pandemi Covid-19 - Armadani Armadani; Abid Ilmun Fisabil; Dexta Tiara Salsabila (Jurnal Akuntansi, 2021)
This research was conducted with the aim of knowing financial distress and bankruptcy predictions in the hotel, restaurant & tourism sub-sector companies during the pandemic of Covid-19 in 2020 using the Altman Z”-Score ratio analysis. The population of this research is all service and hospitality companies listed on the Indonesian Stock Exchange before 2018, the sample was selected based on predetermined purposive sampling criteria. From a sample of 25 companies, using the Z”-Score ratio, it is predicted that there was an increase in the category of bankruptcy (red zone) of 3 companies only within a quarter during the crisis. Companies that were initially included in the safe category as well as having a low risk of bankruptcy (healthy) also decreased, adding 2 companies to the vulnerable category (gray area). This indicates that there are difficulties both financially and in liquidity as well as a decrease in the company's ability to grow, which may lead to bankruptcy. Keywords: Financial Distress, Altman Z”-Score, Bankruptcy, Covid-19.